Job Satisfaction as a Mediator of Workload and Work Stress on Nurse Performance at RSI PKU Muhammadiyah Tegal - Putri Barlian; Akhmad Darmawan; Muchammad Agung Miftahuddin; Amir Amir (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the effect of workload and work stress on the performance of nurses at RSI PKU Muhammadiyah Tegal, with job satisfaction as a mediating variable. This study uses a quantitative approach, with primary data obtained through a questionnaire using Google Form. The study population included 231 nurses and samples were taken using a purposive sampling technique with the criteria of a minimum work period of 2 years and nurses who work in the inpatient room. The number of respondents who met the criteria was 104 nurses. Data analysis was carried out using the SEM PLS3 method. The results of this study indicate that workload and work stress have a positive effect on nurse performance. workload has also been shown to have a positive impact on job satisfaction levels. However, on the contrary, work stress does not show any effect on job satisfaction. In addition, job satisfaction can act as a mediator in the relationship between workload and work stress on nurse performance.